How capital structure, liquidity, and profitability affect on company value (intervening variables studies on food and beverage sub-sector manufacturing companies on idx) - Budiandriani; Mahfudnurnajamuddin; Muh. Haerdiansyah Syahnur (Enrichment : Journal of Management, 2023)
The purpose of this research is to investigate how capital structure and liquidity impact the value of food and beverage companies listed on the Indonesia Stock Exchange, by examining their profitability. The data for this study was obtained from the Stock Exchange Investment Gallery and the Faculty of Economics and Business at the Indonesian Muslim University. The study found that capital structure has a positive and significant impact on profitability in food and beverage companies, while liquidity also has a positive and significant effect on profitability. Additionally, capital structure has a significant and positive impact on firm value, while liquidity has a positive but not significant impact on firm value. Profitability also has a significant and positive impact on firm value in the food and beverage industry. Capital structure has a positive and significant impact on firm value through profitability, while liquidity affects firm value through profitability but does not have a significant impact. The results of this research are expected to be helpful for investors when making investment decisions in food and beverage companies.